The Effectiveness of the Online Cadre Refresh Program on Capacity Building for Cadres in Toddler Posyandu Management During the Covid-19 Pandemic - Ardi Bastian; Reni Nurhidayah; Intan Pratita; Wening Palupi Dewi; Wahyu Purnomo (Journal of Global Research in Public Health, 2023)
One of the health services affected by the COVID-19 pandemic is the toddler posyandu, because that the implementation of toddler growth and development screening was non-optimal. The management of the Toddler Posyandu during the Covid-19 pandemic has its challenges to comply with the established health protocols. There is a need for education and training programs that can improve the ability of cadres to manage toddler posyandu during the COVID-19 pandemic. This study aims to look effectiveness of the cadre refresh program in increasing the ability of cadres to manage the toddler Posyandu during the Covid-19 pandemic. The research design was quasi-experimental with one group pretest posttest approach. The population in this study was 140 toddler cadre Puskesmas Baron Nganjuk with total sampling and using T-test data analysis. The ability of cadres to manage the toddler Posyandu showed an average score of 13.25 before the intervention and 14,75 after program. The result of data analysis indicates there is an effect of online refreshment program on capacity building toddler cadres with ρ-value = 0,000. It is indicate that the cadre refresh program has an impact on increasing the ability of toddler cadres. It was concluded that the cadre refresh program has an impact on increasing the ability of toddler cadres. Re-education will provide a learning experience again so cadres will recall the material they have learned and can broaden their understanding of the material presented by paying attention to updated knowledge and experience that they have experienced.